ENTREPENURICAL BASED EDUCATION (EBD) TO IMPROVE LIFE SKILL COMMUNITY IN BANTEN PROVINCE - Hanafi, Syadeli; Ediwarman, .; Juniardi, Yudi; Wibowo, Firmanul Catur (PEOPLE: International Journal of Social Sciences, 2016)
This study was conducted to achieve the following specific objectives: (a) to obtain data in the process of implementation of automotive training based on partnerships in improving life skills (Life Skills) in Entrepenurical Based Education (EBD) in the Central Services of Non-Formal Education (BPPNF) Banten, ( b) to obtain data on results-based automotive training partnerships in improving life skills on EBL in BPPNF Banten, (c) to obtain a picture of what a limiting factor in the implementation of partnership-based automotive training activities in BPPNF Banten. The method used in this research is descriptive method. The focus is the overall depiction of form, function and meaning of the phrase ban. By using descriptive method, researchers will describe the management BPPNF EBD in Banten Province. Theresearch approach used in this study is a qualitative research. Automotive training processes are carried out in BPPNF Banten including planning, implementation, and evaluation. Automotive training is the result of the increase in employment the trainee's competence after training. Increased job competence aspect is the aspect of skills, aspects of knowledge, aspects of work attitude in the field of automotive motorcycle.